A response spectrum method for peak floor acceleration demands in earthquake excited structures. (October 2016) - Moschen, Lukas; Adam, Christoph; Vamvatsikos, Dimitrios
Abstract: This paper addresses the prediction of the median peak floor acceleration (PFA) demand of elastic structures subjected to seismic excitation by means of an adapted response spectrum method. Modal combination is based on a complete quadratic combination (CQC) rule. In contrast to previous studies, in the present contribution closed form solutions for the correlation coefficients and peak factors entering the CQC rule are derived using concepts of normal stationary random vibration theory. A ground motion set, which matches the design response spectrum for a specific site and a target dispersion, is used to define the stochastic base excitation. The response spectrum method is tested for various planar and spatial generic high-rise structures subjected to this particular ground motion set. A comparison of the outcomes with the results of computationally more expensive response history analyses shows the applicability and accuracy of the proposed simplified method. Highlights: Closed form solution of a response spectrum method for peak floor accelerations. Derivations of cross spectral moments, correlation coefficients, peak factors. Application and evaluation for planar and spatial steel moment resisting frames.